Dimensions and Orientation of Sharia Banking Corporate Social Responsibility In the Society 5.0 - Elmiliyani Wahyuni-S; Revi Candra; Dri Asmawanti-s (Institut Agama Islam Negeri (IAIN) Curup, 2020)
Objective: This article aims to examine the scope of the implementation of Corporate Social Responsibility in Sharia banking as well as orientation that sharia banking should do in the 5.0 Society era.Design/approach: This writing uses a qualitative descriptive approach.Findings: In general, this article succeeded in formulate the form or orientation of Corporate Social Responsibility that should be implemented by sharia banking, more promoting community service that is minimal covering 6 dimensions, namely community settlements, energy, prevention/disaster mitigation, health, food and logistics.Originality/value: This paper is believed to be important and significant especially in an increasingly advanced age. With the emergence of the Society 5.0 is expected to synergize with Sharia banking CSR program to accelerate and provide effectiveness on the social responsibility of sharia banking that is perceived by the community, as well as the input for Sharia banking institutions so that the CSR program should be oriented to the acceleration of social welfare, to provide facilities to the community as a capital to face the global challenge.